El juego participativo para el desarrollo de destrezas psicomotores gruesas en niños de 4 a 5 años de la escuela Miguel Riofrío de la ciudad de Loja, periodo académico 2018-2019 - Masache Torres, Karina del Cisne (2020)
The general objective of the research was to characterize the participatory game as a tool for exploring the medium for the development of gross psychomotor skills in children aged 4 to 5 years, for which the themes related to participatory play and gross psychomotor skills were reviewed; in the development of the research the methods were used; scientific, descriptive, statistical, comparative and analytical-synthetic; To obtain information, a survey was applied to teachers of Initial Level II, to children the OTZERETZKY Test, to diagnose the motor age of children. The investigated population includes two teachers and twenty-one children. The results according to the terminology of the test applied showed the existence of 42.86% of children with motor deficiency, 23.81% with severe motor delay and slight motor delay, presenting difficulties: balance, laterality, coordination of movements, dissociation of movements . To strengthen the development of gross psychomotor skills in children, an alternative proposal was designed and applied with recreational activities such as the participatory game called “How fun it is to play!”; According to the results obtained, it is concluded that participatory play contributes as a methodological strategy for the development of gross psychomotor skills in children and guides teachers to know their importance as a didactic strategy in the classroom.